Wo - Wyss - Kosch, Wilhelm,Achnitz, Wolfgang,Hagestedt, Lutz,Müller, Mario,Ort, Claus-Michael,Sdzuj, Reimund B. (De Gruyter, 2014)
The Deutsches Literatur-Lexikon is one of the best known, most comprehensive and most reliable reference works on German literature. The scope of the Deutsches Literatur-Lexikon is simply unrivalled: Spanning the ages, the work encompasses writers from all eras, ranging from the Middle Ages to the present day. The work presents writers from the Federal Republic of Germany, the former German Democratic Republic, Switzerland and Austria, as well as German-language writers from other European countries. Articles contain full name, dates of birth and death and a short biography. The bibliographical section provides details on writings, translations, editorial activities, editions, letters, estate, compilations, bibliographies, research reports and academic studies, general portraits and appreciations as well as on secondary literature focussing on individual works.
Description based on publisher supplied metadata and other sources